Pinching Theorems for a Vanishing C-Bochner Curvature Tensor - Jae Won Lee; Chul Woo Lee (Mathematics, 2018)
The main purpose of this article is to construct inequalities between a main intrinsic invariant (the normalized scalar curvature) and an extrinsic invariant (the Casorati curvature) for some submanifolds in a Sasakian manifold with a zero C-Bochner tensor.